Optimization of Drying Temperature in the Production Process of Tea Seed Oil - Hafids, Sahrial (Department of Technology of Agricultural product (THP) Jambi University, 2018)
This study aims to determine the optimal temperature for drying kernel flour from tea seeds which will be used as raw material in the production of tea seed oil (TSO) by maceration method using n-hexane solvent. The study used a completely randomized design with 6 treatments for drying temperatures, namely: 60, 70, 80, 90, 100, and 110oC. The results showed that the optimal temperature for drying kernel flour from tea seeds was 80oC with a drying time of 3.5 hours. At the optimum temperature obtained TSO yield of 16.12% with free fatty acid content of 0.40%, iodine number 30.16 g I2/100 g of material, peroxide number 0.16 meq KOH /100 g, saponification number 144.55 mg KOH/g TSO, specific gravity 0.94 g/ml, refractive index 1.67, and melting point 2.0oC.